ASSAY AND GRAPHITE FURNACE- ATOMIC ABSORBANCE SPECTROMETRY ACCURACY FOR PALLADIUM CONTENT ANALYSIS - Ronaldo Irzon; Kurnia (BRIN, 2021)
Palladium is a member of the expensive Platinum Group Metals as it is indispensable for various applications of modern technology. Due to the very small number of these elements in nature, high-sensitivity analytical methods and devices are required for accurate PGM measurement. The current study aims to determine the accuracy level of the Graphite Furnace-Atomic Absorbance Spectrometry device for palladium analysis after pre-concentration through the assaying process. The studied samples were two in-house standard reference samples with stream sediment and ultramafic rock matrices. Due to the lack of certified reference material containing certain palladium compositions, the degree of accuracy was tested by the spiking method. The detection limit for Pd in this study was 11.79 ppb. Pd content in the stream sediment (17 ppb) is much lower than of the ultramafic sample (290 ppb), implying PGM association to ultramafic rock naturally. Almost all measurements have good accuracy according to spike recovery between 80-120%. Inaccurate addition process and inappropriate calibration range most probably lead to inaccuracy.